Modernizing Islamic Higher Education: Strategic Challenges and Innovations at Ma’had Aly Lirboyo Kediri - Rahmadani, Desy Rita; Nurhidin, Edi (Journal of Pesantren and Diniyah Studies, 2025)
The rapid development of technology and globalization significantly affects the quality of educational institutions, particularly the quality of education at Ma'had Aly, which is steeped in the salaf traditions. To ensure the quality of education at Ma'had Aly can keep pace with the needs of the times, educational modernization is necessary by adapting and integrating technology with tradition. Every new change will inevitably face various challenges and problems. This article aims to describe the various challenges and innovations in modernizing education. This study uses a descriptive qualitative research method at Ma'had Aly Lirboyo Kediri. This study found that Ma'had Aly Lirboyo has endeavored to modernize its education despite facing various challenges. In addition to challenges, the educational modernization at Ma'had Aly Lirboyo also creates opportunities to improve its quality and relevance to societal needs and contemporary challenges. Forms of modernization and innovation include the use of technology during lectures, innovative curriculum development, the use of active learning strategies, collaboration with other universities both domestically and internationally, development of research and community service, the use of social media and digital platforms, and the development of information systems. It can be concluded that by utilizing challenges and opportunities and efforts to overcome them, Ma'had Aly Lirboyo can improve the quality of education following current developments and increase the relevance of education for students.